(3GdTaGAs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3BNQgG (B:s
(3JfJgi HGdOdjd hGdYdGeI hGdaQGSI s
(3GdfSNI HgG MhGTs
(3bSe GdefWbs
(3fSNI YGTQIs
(3jfbUgG ef Chd GdHQgGf s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdadSaI hGdefWbs